Immunoinflammatory Response in Critically Ill Patients: Severe Sepsis and/or Trauma - Maja Surbatovic; Milic Veljovic; Jasna Jevdjic; Nada Popovic; Dragan Djordjevic; Sonja Radakovic (Mediators of Inflammation)
Immunoinflammatory response in critically ill patients is very complex. This review explores some of the new elements of immunoinflammatory response in severe sepsis, tumor necrosis factor-alpha in severe acute pancreatitis as a clinical example of immune response in sepsis, immune response in severe trauma with or without secondary sepsis, and genetic aspects of host immuno-inflammatory response to various insults in critically ill patients.